ANALISA PENGARUH KINERJA LINGKUNGAN TERHADAP KINERJA PASAR: PERSPEKTIF UKM DI PONTIANAK - Ema Trisnawati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
Environmental issues such as climate change have made it impossible for companies to focus solely on financial performance without considering their ecological impacts. Government regulations and stakeholder demands require companies to manage and minimize the environmental impacts of their operations. Environmental performance refers to a company's ability to reduce pollution, waste, and the use of hazardous materials through proper environmental management practices. This study aims to analyze the influence of environmental performance on the market performance of Small and Medium Enterprises (SMEs) in Pontianak, Indonesia. A quantitative survey was conducted involving 56 SMEs. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that environmental performance has a positive and significant influence on market performance, with an R-square value of 0.886. This implies that enhancing environmental management practices can improve SME market outcomes in Pontianak. The findings provide guidance for SME managers on developing green strategies to meet organizational goals and stakeholder expectations as well as achieve environmental sustainability. Key word: Environmental Performance, Market Performance, SME’s